Protocol for a randomized trial on nausea, vomitus and arterial hypotension comparing carbetocin and oxytocin as prevention for hemorrhage after cesarean section - A., Verster; D., Mannaerts; Veken L., Van Der; K., De Maeyer; H., Coppejans; Y., Jacquemyn (International Journal of Clinical Trials, 2017)
Background: To prevent hemorrhage after cesarean section uterotonics are often administered after fetal extraction. At this moment two frequently used and available products are short working oxytocin and its long working analogue, carbetocin. Both have proven and similar efficacy. Side effects are nausea, vomitus and arterial hypotension resulting in dizziness. Differences in nausea, vomitus and blood pressure changes between oxytocin and carbetocin have been studied as secondary outcome measures only and results have been conflicting. The aim of the present study is to compare nausea, vomiting and changes in blood pressure between carbetocin and oxytocin used as prevention for postpartum hemorrhage after cesarean section. Methods: Patients are women undergoing a planned term cesarean section for singleton pregnancy without other medical complications. One hundred patients will be randomized to receive either a single intravenous dose of 100 microgram carbetocin, either an intravenous bolus of 5 units of oxytocin followed by 10 units of oxytocin over 24 hours. As primary outcome nausea and vomitus are evaluated before, during and immediately after surgery, using a standard scale, blood pressure is automatically measured every three minutes. Secondary outcome measures are the difference between pre- and postoperative hemoglobin and the need for additional uterotonics. Analysis will be based on intention to treat. Conclusions: This study will offer data on the difference in clinically relevant side effects between carbetocin and oxytocin helping clinicians to choose between both products in low risk cesarean sections.